Securing the Payload, Finding the Cell, and Avoiding the Endosome: Peptide‐Targeted, Fusogenic Porous Silicon Nanoparticles for Delivery of siRNA. Issue 35 (3rd July 2019) - Kim, Byungji; Sun, Si; Varner, Judith A.; Howell, Stephen B.; Ruoslahti, Erkki; Sailor, Michael J.
Abstract: Despite the promise of ribonucleic acid interference therapeutics, the delivery of oligonucleotides selectively to diseased tissues in the body, and specifically to the cellular location in the tissues needed to provide optimal therapeutic outcome, remains a significant challenge. Here, key material properties and biological mechanisms for delivery of short interfering RNAs (siRNAs) to effectively silence target‐specific cells in vivo are identified. Using porous silicon nanoparticles as the siRNA host, tumor‐targeting peptides for selective tissue homing, and fusogenic lipid coatings to induce fusion with the plasma membrane, it is shown that the uptake mechanism can be engineered to be independent of common receptor‐mediated endocytosis pathways. Two examples of the potential broad clinical applicability of this concept in a mouse xenograft model of ovarian cancer peritoneal carcinomatosis are provided: silencing the Rev3l subunit of polymerase Pol ζ to impair DNA repair in combination with cisplatin; and reprogramming tumor‐associated macrophages into a proinflammatory state. Abstract : Fusogenic porous silicon nanoparticles enable ribonucleic acid interference therapeutics by effectively delivering their short interfering RNA payload to selectively targeted cells in vivo to induce significant gene silencing. These particles represent a generalizable platform technology that can be modified in a facile manner into different formulations; two model therapeutics (gene therapy and immunotherapy) are demonstrated to treat ovarian cancer.